Analytical methodology to screen UV-filters and synthetic musk compounds in market tomatoes. (January 2020) - Ramos, Sara; Homem, Vera; Santos, Lúcia
Abstract: A Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) methodology followed by gas chromatography-tandem mass spectrometry (GC-MS/MS) analysis was developed to extract thirteen synthetic musk compounds (SMCs: cashmeran, celestolide, phantolide, traseolide, galaxolide, tonalide, musk ambrette, musk xylene, musk ketone, musk tibetene, musk moskene, ethylene brassylate and exaltolide) and six ultraviolet-filters (UVFs: 2-ethylhexyl 4-dimethylaminobenzoate, 3-(4′-methylbenzylidene) camphor, 2-ethylhexyl 4-methoxycinnamate, 2-ethylhexyl 2-cyano-3, 3-diphenylacrylate, benzophenone and drometrizole trisiloxane) from tomatoes. The proposed methodology was optimized: 2 g of freeze-dried tomato was extracted with 4 mL of water and 10 mL of ethyl acetate, adding 6 g of MgSO4 and 1.5 g of NaCl, then a dispersive solid-phase extraction was performed using 3 g of MgSO4, 300 mg of primary-secondary amino adsorbent (PSA) and 300 mg of octadecyl-silica (C18). Validation delivered recoveries between 81 (celestolide) and 119% (musk tibetene), with relative standard deviations <10%. The instrumental limit of detection varied from 0.02 (2-ethylhexyl 4-methoxycinnamate) to 3.00 pg (exaltolide and musk xylene). Regarding the method quantification limits, it ranged between 0.4 (celestolide) and 47.9 ng g −1 dw (exaltolide). The method was applied to different varieties of tomatoes ( Solanum lycopersicum ), revealing UVFs and SMCs between 1 and 210 ng g −1 dw. Higher concentrations were found for benzophenone (29–210 ng g −1 dw) and galaxolide (9–53 ng g −1 dw). The risk associated to the ingestion of contaminated tomatoes has also been estimated, showing that a potential health risk is unlikely. Graphical abstract: Image 1 Highlights: Ultraviolet filters and synthetic musk compounds were detected in market tomatoes. The method was optimized and validated for 19 compounds. Good precision (<10%), accuracy (97 ± 10%) and low limits of detection were found. No matrix effects were observed in the extraction of the compounds from tomato. Based on the risk assessment performed, there's no potential health risk associated.